Feedback - Arndt Niebisch (Semiotic Review)
The twentieth century saw a tremendous change in modes of mass communication. The circuits of social exchange were predominantly enhanced and amplified through the new circuitry that electrical engineering provided. From that point on, the hegemonies of communication shifted from writing and aurality to the ether of electromagnetic transmission, where messages did not only become transmittable over vast distances, but where they also could be modified and amplified. The key technology that should even increase the dominance of electromagnetic transmission, the vacuum tube, did not only improve the transmission and reception technologies of the radio, but also enabled the construction of unique sonic events as well as the amplification through feedback, where a signal became repeatedly fed back into the circuit that it produced in the first place. In the age of feedback, messages do not have to be an original product, but they have to resonate infinitely through the echo chambers of discourse. This nature of modern means of communication brings us directly to the topic of the parasite. The French theorist and historian of science Michel Serres identified feedback as a parasitical structure; it does not create an own performance but takes its own mirror image as a place of departure. In this article I discuss two examples from the twentieth century avant-garde to show how feedback was employed as an aesthetic strategy for social manipulation. I first outline the parasitical strategies of Dada performances in the early twentieth century and then, second, I focus on the project of a subversive media tactics as suggested by the famous experimental writer William S. Burroughs in his text The Electronic Revolution.